Cardioprotective Effect of Propofol against Oxygen Glucose Deprivation and Reperfusion Injury in H9c2 Cells. (4th March 2015) - Zhao, Dandan; Li, Qing; Huang, Qiuping; Li, Xuguang; Yin, Min; Wang, Zejian; Hong, Jiang
Abstract : Background . The intravenous anesthetic propofol is reported to be a cardioprotective agent against ischemic-reperfusion injury in the heart. However, the regulatory mechanism still remains unclear. Methods . In this study, we used H9c2 cell line under condition of oxygen glucose deprivation (OGD) followed by reperfusion (OGD/R) to induce in vitro cardiomyocytes ischemia-reperfusion injury. Propofol (5, 10, and 20 μ M) was added to the cell cultures before and during the OGD/R phases to investigate the underlying mechanism. Results . Our data showed that OGD/R decreased cell viability, and increased lactate dehydrogenase leakage, and reactive oxygen species and malondialdehyde production in H9c2 cells, all of which were significantly reversed by propofol. Moreover, we found that propofol increased both the activities and protein expressions of superoxide dismutase and catalase. In addition, propofol increased FoxO1 expression in a dose-dependent manner and inhibited p-AMPK formation significantly. Conclusions . These results indicate that the propofol might exert its antioxidative effect through FoxO1 in H9c2 cells, and it has a potential therapeutic effect on cardiac disorders involved in oxidative stress.